Burnout among Physicians at Medical Departments in Benghazi-Libya - Alsaeiti, Khaled D.; Elkadiki, Abdelhdi; Hamedh, Mohamed A. I.; Ezwaie, Ragheda M.; Younis, Sarah Muftah; Elfigih, Seraj O. (Libyan International Medical University Journal, 2022)
Background Burnout syndrome is recognized as a global issue, and as medical practice is stressful, healthcare workers are found to be burnt out and exhausted very soon, which is reflected negatively on the medical staff well-being, patients' outcome, and the overall organizational performance.Aim This study is planned to assess the magnitude of burnout among physicians in Benghazi-Libya.Methods This cross-sectional study was carried out in 2020 on a total of 150 physicians working at different departments of internal medicine in Benghazi-Libya. The Maslach Burnout Inventory collection instrument was used to assess the three components of burnout syndrome: emotional exhaustion, depersonalization, and reduced personal accomplishment. High scores in emotional exhaustion and depersonalization and low scores in personal accomplishment are indicative of high burnout. The statistical analyses of the data were performed using the SPSS version 21. The level of statistical significance was considered as p-value less than 0.05.Results 60% of the respondents were females and 40% were males. About 14.7% had high emotional exhaustion, 92% had high depersonalization, and 87.3% had low personal accomplishment scores. Statistical analysis showed no significant relationship between gender and burnout. Alternatively, a significant association was found between degree certificate and emotional exhaustion, as moderate- and high-level burnout were more prevalent among MBCHB participants than those with masters and board degrees. No association was found between degree certificate and depersonalization or personal accomplishment.Conclusion Burnout is prevalent among internal medicine doctors in Benghazi, with the newly graduated medical personnel scoring higher rates of burnout than doctors with higher degrees. No relationship was found between gender and burnout.
Keywords: burnout; Benghazi; Libya; physician; Maslach